Project Management as a Factor of International Competitiveness of Finland - Hristova, Antoaneta (Research Papers, 2009)
The rise in productivity and the achievement of sustainable economic growth require clear organizational and managerial vision. The Finnish Government unambiguously declares that the attainment of sustainable international competitiveness presupposes changes in working methods, and recommends the application of Project Management as a reasonable management approach at company, at municipality and at central Government level. The sophistication of knowledge and skills for managing a well-considered portfolio of programs and projects, prioritized according to their contribution to the achievement of economic growth, employment and international competitiveness, is a national goal in Finland.Through the adoption of Project Management as a management approach, the central state administration in Finland strives to be a pioneer in the development of organizational and managerial capacity, and to be a catalyst for Project Management dissemination among the municipalities and the private sector. In Finland, Project Management is a means of communication which facilitates and optimizes the interaction among stakeholders. The constructive national dialogue contributes to the overall competitiveness of the contemporary democratic country.